Carbon Nanodot Surface Modifications Initiate Highly Efficient, Stable Catalysts for Both Oxygen Evolution and Reduction Reactions. Issue 9 (8th February 2016) - Liu, Juan; Zhao, Shunyan; Li, Chuanxi; Yang, Manman; Yang, Yanmei; Liu, Yang; Lifshitz, Yeshayahu; Lee, Shuit‐Tong; Kang, Zhenhui
Abstract : Efficient, stable, and low‐cost electrocatalysts for the oxygen evolution and reduction reactions (OER and ORR) are essential components of energy conversion. Although much progress has been achieved in the development of platinum‐based electrocatalysts for ORR and iridium‐based electrocatalysts for OER, they are still not yet viable for large‐scale commercialization because of the high cost and scanty supply of the noble metals. Here, it is demonstrated that carbon nanodots surface‐modified with either phosphorus or amidogen can respectively achieve electrocatalytic activity approaching that of the benchmark Pt/C and IrO2 /C catalysts for ORR and OER. Furthermore, phosphorus (amidogen)‐modified carbon nanodots with attached Au nanoparticles exhibit superior ORR (OER) activity better than commercial Pt/C (IrO2 /C) catalysts as well as excellent electrochemical stability under visible light. Abstract : Metal‐free carbon nanodots surface‐modified with either phosphorus or amidogen can respectively achieve superior electrocatalytic activity approaching and even exceeding that of the benchmark Pt/C and IrO2 /C catalysts for oxygen reduction reactions (ORR) and oxygen evolution reactions (OER). Attaching Au nanoparticles on these catalysts will further enhance their electrocatalytic activities under visible light.